Strobilanthes: Panicled species from East Asia - Wood, J; Scotland, R (2003)
The species of Strobilanthes from East Asia with a paniculate inflorescence form a readily identifiable cluster of species, which reaches its greatest diversity on the Indonesian Island of Sumatra. The 16 species are enumerated, described and discussed. Three new species, Strobilanthes ramosissima (from Sumatra), S. tenuiflora (from Thailand) and S. euantha (from the China-Burma (Myanmar) border region) are described, a new name, S. bunnemeyeri is provided for Diflugossa glandulosa, and the new combinations S. ovatifolia and S. pubescens are made. A key is provided to facilitate identification. Several species are illustrated for the first time and maps show the distribution of all species discussed in this paper.